Developing a Fun Cooking Guidebook to Build Reading and Writing Literacy in Children Aged 5–6 Years - Daryani, Sri; Debie Susanti; Sri Watini (UNIB Press, 2025)
The absence of organized teaching aids for cooking activities prevents teachers from fully promoting comprehensive development in young children at the preschool level. Enriches children s mind, moral values, and cognitive growth, interest in learning, and social life. Attractive cookware playsets to inspire kids' imagination. The present study aims to design and evaluate the applicability of a fun cooking manual kit as an educational approach for a kindergarten course. The study employed a Research and Development (R&D) design using the 4D model: Define, Design, Develop, and Disseminate. The Define stage comprised a needs analysis of teachers and classroom activities. In contrast, the Design and Develop stages involved the design, development, and expert validation of the guidebook, with Disseminate comprising small implementation trials. Data were collected through questionnaires, expert validation sheets, and observation checklists used to assess teachers' personalities at the Child Asmaul Husna Kindergarten in Tangerang. The average feasibility score across four experts (nutrition, culinary arts, media, and early childhood education) was 3.6 (89.5%), indicating high feasibility and satisfaction with pedagogical, nutritional, and practical requirements. Trial results indicated that children became better critical thinkers, more creative, and more independent. In summary, the fun cooking guidebook, in accordance with the center method , is practicable and effective in cultivating infants' comprehensive capacity.